Relationship between IADL, physical function, physical activity, and fall-related efficacy among older people using daycare centers - Masahiro Kitamura; Kazuhiro P. Izawa; Kyohei Kurihara; Sayaka Yamamoto; Satoshi Ozawa; Erina Uchida; Junichi Umeo (Discover Public Health)
Key summary points Aim The purpose of this study was to provide intervention measures for maintaining and improving the instrumental activities of daily living (IADL) of older people using daycare centers by identifying factors related to IADL. Findings A timed up and go test time ≥11.6 sec, light physical activity (LPA) ≤193 min/day, or fall-related efficacy ≤125.5 points flags daycare users at high risk of IADL decline. Message Daycare staff could screen daycare users using these indices and then provide them with exercises to improve balance function, LPA, and fall-related function, potentially helping to maintain or improve their IADL.